MOTIVATION AND PERCEPTION OF THE STUDENTS TOWARD THE ENGLISH TEACHER AS THEIR FUTURE CAREER - Martriwati Martriwati; Burhayani Burhayani (UICELL, 2021)
Researches about students’ teaching motivation and their perception toward teacher profession have been conducted widely abroad but there are not many similar researches available in Indonesia. Seeing the lack of the research the writer conducted it which has the aims to describe the motivations and perceptions of the students in choosing the English Study Program of UHAMKA which mainly focuses on producing the candidate of English teacher. This study is a descriptive qualitative study with the sample size of 120 freshmen students and 50 alumni. The data were collected through questionnaires and interview. The finding of the research is hoped can be used by English Study Program of UHAMKA in doing changing of promotion for getting new students. Furthermore, the results of the study can be useful as an input in managing the curriculum and the service to the students such as changing the teaching techniques so the students’ motivation to be an English teacher could be improved. Keywords: perception, motivation, teacher profession